2016
DOI: 10.1097/md.0000000000004114
|View full text |Cite
|
Sign up to set email alerts
|

Urinary N-acetyl-β-D-glucosaminidase, an early marker of diabetic kidney disease, might reflect glucose excursion in patients with type 2 diabetes

Abstract: Recently, several renal tubular damage markers have gained considerable attention because of their clinical implications as sensitive and specific biomarkers for early stage diabetic kidney disease. However, little is known about the demographic and glucometabolic factors affecting levels of urinary N-acetyl-β-d-glucosaminidase (NAG), a marker of proximal tubular damage, in type 2 diabetes mellitus (T2DM).The aim of this study was to investigate the clinical relevance of urinary NAG with regard to demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 36 publications
1
39
2
1
Order By: Relevance
“…Similarly, a research conducted by Bouvet et al 10 also revealed a strong and statistically significant correlation between urine NAG and UACR (r=0.628) (p<0.001) in type 2 DM patients. Unlike the research conducted by Bouvet et al, a research conducted by Kim et al 11 showed a moderate and statistically significant correlation between urine NAG and UACR (R=0.458) (p<0.001) in patients with type 2 DM.…”
Section: Resultscontrasting
confidence: 64%
See 3 more Smart Citations
“…Similarly, a research conducted by Bouvet et al 10 also revealed a strong and statistically significant correlation between urine NAG and UACR (r=0.628) (p<0.001) in type 2 DM patients. Unlike the research conducted by Bouvet et al, a research conducted by Kim et al 11 showed a moderate and statistically significant correlation between urine NAG and UACR (R=0.458) (p<0.001) in patients with type 2 DM.…”
Section: Resultscontrasting
confidence: 64%
“…16 Nevertheless, this research did not measure BMI of each research subject. Thus, the different median values of UACR in this research from those in the previous researches conducted by Piwowar et al 12 and Kim et al 11 may be related to differences in GFR and BMI of the research subjects.…”
Section: Resultscontrasting
confidence: 53%
See 2 more Smart Citations
“…18,19 The role of insulin indices as DR biomarker is of increasing interest. 20 We expected that subclinical microvascular abnormalities of the macula appearing on OCT-A assessments might serve as a noninvasive and useful biomarker showing a significant correlation with some of the most representative and common existing biomarkers of DR.…”
mentioning
confidence: 99%